Dephytinizing and probiotic potentials of saccharomyces cerevisiae (NCIM 3662) strain for amelioration of nutritional quality of functional foods - Kumar Raja Puppala; Kumar , V. Ravi; Khire, Jayant; Dharne, Mahesh (Probiotics and Antimicrobial Proteins, 2018)
Increase of undigested complexes of phytic acid in food is gaining serious attention to overcome nutritional challenges due to chelation effects. We investigated soil-borne yeast phytase from Saccharomyces cerevisiae (NCIM 3662) for dephytinization of foods, probiotic properties, and process development. The strain produced 45 IU/DCG by cell-bound phytase in an unoptimized medium was increased fourfold (164 IU/DCG) in 12 h using statistical media optimization. The process was scaled-up up to 10-L fermenter scale with increased phytase productivity of 6.4 IU/DCG/h as compared to the lab scale. The strain displayed probiotic characteristics like tolerance to artificial gastric acid conditions, hydrophobicity, autoaggregation, coaggregation, and bile salt hydrolase (BSH) activity. Further, it could dephytinize (removal of phytic acid; an anti-nutritional factor) functional foods like ragi (finger millet) flour, soya flour, chickpea flour, and poultry animal feed. A combination of cell-bound dephytinizing phytase and nutrition-ameliorating probiotic traits of S. cerevisiae (NCIM 3662) presents profound applications in food technology sector.